Faculty development workshop on gender‐associated incivility in nursing education. Issue 4 (30th May 2021) - Smallheer, Benjamin; Gedzyk‐Nieman, Stephanie A.; Molloy, Margory A.; Clark, Cynthia M.; Gordon, Helen; Morgan, Brett
Abstract: Background: Men comprise the minority of entry‐level baccalaureate nursing students and are at increased risk of experiencing gender‐associated incivility. Problem: Uncivil peer‐to‐peer behavior can negatively affect students' mental and physical well‐being, and learning experience. Nursing faculty must be able to identify and address gender‐associated incivility among students. Aim: The purpose of this quality improvement program was to train nursing faculty to prevent, identify, and manage gender‐associated incivility in the educational environment. Methods: A day‐long interactive workshop utilizing trigger films, small group discussions, and interactive theater was developed to train nursing faculty to implement proactive and reactive techniques to address uncivil behavior which will enhance the learning environment for all students. Utilizing Kirkpatrick's Model of Evaluation, participants were surveyed at the conclusion of the workshop and four months postworkshop to evaluate their learning and its implementation. Results: Participants gained greater understanding of the impact of gender‐associated incivility and felt both empowered and better prepared to manage gender‐associated conflict. Conclusion: Similar approaches may be useful for schools of nursing that wish to empower their nursing faculty to support an equitable nursing education environment free of gender‐associated incivility.